Anti-glare film, and method for producing and using the same
By preparing an anti-glare film with an absolute value of chromaticity b* of transmitted light and a haze of less than 15 and an anti-glare layer of more than 30%, using the combination of polymer and cured resin precursor components, the anti-glare layer was formed by decomposing the spiral joint line, and the solution was solved In the prior art, the problem of difficulty in taking into account both anti-glare properties and transparency is realized, and a film with high anti-glare properties and transparency is realized.
Patent Information
- Application Number
- CN202210637196.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-11
- Filing Date
- 2018-09-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2038-09-21
AI Technical Summary
The existing anti-glare film can easily lead to a decrease in anti-glare properties when improving transparency, and it is difficult to take into account both anti-glare properties and transparency, especially the suppression of yellow feeling.
By preparing an anti-glare film with an absolute value of 15 or less and a haze of 30% or more, a curable composition containing more than one polymer component and more than one curing resin precursor component is used to prepare an anti-glare film with an absolute value of 15 or less and a haze of 30%. , the anti-glare layer is formed by decomposing wet spiral joints.
It is realized that anti-glare properties are improved while suppressing the yellow feeling, taking into account anti-glare properties and transparency, especially in the display device to improve visual recognition.
Smart Images

Figure BDA0003680875520000211
Abstract
Description
[0001] This application is a divisional application of an application with an application date of September 21, 2018, application number 201880078700.9, and invention name “Anti-glare film, and its manufacturing method and use”. Technical Field
[0002] The present invention relates to an anti-glare film which can be used in various display devices such as a liquid crystal display (LCD) and an organic electroluminescent (EL) display, as well as a method for producing the same and use thereof. Background Art
[0003] Anti-glare films have been widely used as films for preventing the outside world from being reflected into the display surface of image display devices such as LCDs and organic EL displays, and for improving visual recognition. As optical properties required of anti-glare films, in addition to the function of improving anti-glare properties by having high haze, the characteristics of having high transparency (total light transmittance) and imparting a neutral white tone to the visible side instead of yellowish or reddish light to improve visual recognition can also be cited. In order to exhibit such functions, the following method is known for anti-glare films: by coating a mixture of microparticles and a binder resin or a curable resin on a substrate, fine concave-convex surfaces are formed on the surface, thereby preventing specular reflection and exhibiting anti-glare properties. However, in anti-glare films using microparticles, since the intensity distribution of transmitted scattered light is controlled according to the particle size, it is not possible to effectively prevent glare on the display surface and blurred text. In addition, for anti-glare films with dispersed particles, the greater the difference in refractive index between the base material constituting the anti-glare film and the dispersed particles, the higher the haze value and the higher the light diffusivity. However, as the internal haze increases, the light on the short wavelength side is scattered toward a wide angle. Therefore, when the display device is viewed from the front, yellowing and dullness are observed, and visual recognition is reduced. In addition, since backscattering is likely to occur, the transparency is also reduced.
[0004] For this purpose, there is also a known method of forming a concavo-convex shape on a surface by using the spinodal decomposition of an incompatible resin component. In Japanese Patent Publication No. 2014-85371 (Patent Document 1), an anti-glare film is disclosed, which includes an anti-glare layer having elongated convex portions formed on the surface by phase separation of a plurality of resin components, wherein the elongated convex portions have a branched structure and a total length of 100 μm or more, and on the surface of the anti-glare layer, on average, 100 μm of the convex portions are formed per 1 mm. 2 The anti-glare film has an excellent balance between haze and sharpness, and even when it is arranged on a high-definition display device (such as an LCD or organic EL display with a resolution of 200 ppi or more), the anti-glare property can be improved, glare can be highly suppressed, and text blur can be suppressed.
[0005] However, for the anti-glare film, the anti-glare property may be reduced when the transparency is improved. In addition, in the existing method, in order to improve the anti-glare property, it is necessary to improve the light scattering and adjust to a high haze, but the anti-glare property and transparency (especially the suppression of yellow sense) are in a compromise relationship and are difficult to take into account.
[0006] In Japanese Patent Gazette No. 5531388 (Patent Document 2), as a method for stably supplying an optical sheet with good contrast, a method for manufacturing an optical sheet is disclosed, wherein the optical sheet has a functional layer on at least one side of a transparent substrate, and has a diffusion element on the outermost surface and / or inside of the functional layer. The method includes: controlling so that the ratio of the diffuse light specular reflection intensity measured at a given angle to the sum of the diffuse reflection intensities exceeds 0.19, thereby stably manufacturing an optical sheet with excellent contrast.
[0007] However, it is also difficult to improve the transparency of the optical sheet obtained by this method.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-85371 (Claim 1, paragraph
[0021] )
[0011] Patent Document 2: Japanese Patent No. 5531388 (Claim 1) Summary of the invention
[0012] Problems to be solved by the invention
[0013] Therefore, an object of the present invention is to provide an anti-glare film having less yellowish tinge and high anti-glare property, and a method for producing the same and use thereof.
[0014] Solutions to the problem
[0015] The present inventors have conducted intensive research to achieve the above-mentioned objectives and have found that: * The present invention has been completed by an anti-glare film having an absolute value of 15 or less and a haze of 30% or more, which can improve anti-glare properties while suppressing yellowness.
[0016] That is, the chromaticity b of the transmitted light of the anti-glare film of the present invention is * The absolute value of is less than 15, and the haze is more than 30%. The anti-glare film may also be a chromaticity b of the transmitted light. *The absolute value of is 3 or less, and the 60° glossiness is 25% or less. The anti-glare film may include a transparent substrate layer, and an anti-glare layer formed on at least one side of the transparent substrate layer, and the anti-glare layer is a cured product of a curable composition containing one or more polymer components and one or more curing resin precursor components. It may be that at least two components selected from the polymer components and the curing resin precursor components can be phase-separated by wet spinodal decomposition. The polymer components may contain cellulose esters and / or (meth) acrylic polymers optionally having polymerizable groups. The curing resin precursor component may contain at least one selected from multifunctional (meth) acrylates, epoxy (meth) acrylates, polyester (meth) acrylates, urethane (meth) acrylates and silicone (meth) acrylates. The curing resin precursor component may contain silica nanoparticles and / or fluorine atoms.
[0017] The present invention also includes a method for producing the anti-glare film, which includes: a curing step of curing the curable composition by heat or active energy rays. The manufacturing method may further include: a phase separation step of applying a curable composition containing one or more polymer components and one or more curable resin precursor components on a support and drying the curable composition, so that at least two components selected from the polymer components and the curable resin precursor components undergo phase separation by wet spinodal decomposition. The curing step may be a curing step of curing the curable composition after phase separation by heat or active energy rays.
[0018] The present invention also includes a display device having the anti-glare film. The display device may be an organic EL display or a liquid crystal display.
[0019] The present invention also includes the chromaticity b of the transmitted light * The absolute value of and the haze are adjusted to be less than 15 and more than 30% respectively to improve the anti-glare property and transparency of the anti-glare film.
[0020] It should be noted that in the present specification and claims, (meth)acrylate includes both methacrylate and acrylate.
[0021] Effects of the Invention
[0022] In the present invention, since the absolute value of the chromaticity b* of the transmitted light of the anti-glare film is less than 15 and the haze is more than 30%, both the color tone (non-coloring) and the anti-glare property can be achieved. In particular, the yellowness can be reduced, and the anti-glare property can be improved while suppressing the yellow feeling. DETAILED DESCRIPTION
[0023] [Optical properties of anti-glare films]
[0024] The anti-glare film of the present invention has a chromaticity b of the transmitted light. * The absolute value of and haze are adjusted to a specific range, so that both anti-glare and transparency (especially suppression of yellowing) can be achieved.
[0025] The anti-glare film of the present invention only needs to have a chromaticity (transmitted hue) of the transmitted light b * The absolute value of may be 15 or less (e.g., 0 to 15), for example, 10 or less (e.g., 5 or less), preferably 3 or less, more preferably 2 or less, and particularly preferably 1 or less (e.g., 0.1 to 1). Chromaticity b * When the value exceeds 15, the yellowish and blueish tones increase, the product looks dull, and the transparency decreases.
[0026] It should be noted that in this specification and claims, the color b * The measurement can be performed using a spectrophotometer ("U-3010" manufactured by Hitachi High-Tech Science Co., Ltd.) in accordance with JIS Z8781.
[0027] The anti-glare film of the present invention may have a haze of 30% or more (e.g., 30 to 100%), but from the perspective of improving the anti-glare property, it may be, for example, 40% or more (e.g., 40 to 99%), preferably 50 to 98% (e.g., 70 to 97%), and more preferably 80 to 96% (particularly preferably 85 to 95%). If the haze is too low, the anti-glare property may be reduced.
[0028] The total light transmittance of the antiglare film of the present invention is, for example, 70% or more (eg, 70 to 100%), preferably 80 to 99.9%, more preferably 85 to 99% (particularly preferably 90 to 98%). If the total light transmittance is too low, the transparency may be reduced.
[0029] In addition, in this specification and claims, haze and total light transmittance can be measured according to JIS K7105 using a haze meter ("NDH-5000W" manufactured by Nippon Denshoku Industries Co., Ltd.).
[0030] [Anti-glare layer]
[0031] The anti-glare film of the present invention only needs to include an anti-glare layer for exhibiting the above-mentioned optical characteristics. The material and structure are not limited, but it is usually formed of a transparent material with fine concavo-convex shapes formed on the surface. The concavo-convex shapes can suppress the reflection of external scenes caused by surface reflection, thereby improving the anti-glare property.
[0032] The 60° glossiness of the surface of the anti-glare layer (at least one surface when the anti-glare film is formed by the anti-glare layer alone) may be 90% or less, for example, 0 to 25%, preferably 0.1 to 20% (for example, 0.2 to 10%), and more preferably 0.3 to 5% (particularly preferably 0.5 to 1%). If the 60° glossiness is too high, there is a risk of reduced anti-glare properties.
[0033] In the present specification and claims, the 60° glossiness can be measured in accordance with JIS K8741 using a gloss meter ("G-320" manufactured by Horiba, Ltd.).
[0034] The anti-glare film of the present invention may be formed of an anti-glare layer alone, or may include a transparent base layer and an anti-glare layer formed on at least one surface of the transparent base layer.
[0035] The anti-glare layer may be formed of a transparent material, or may be formed of any material of an organic material and an inorganic material, but in terms of productivity, handling, etc., an anti-glare layer formed of a composition containing a resin component is preferred. The surface of the anti-glare layer generally has a concavo-convex shape, which is not particularly limited and may be a concavo-convex shape formed by physical processing, transfer using a mold, etc., but in terms of productivity, etc., in the anti-glare layer formed of a composition containing a resin component, a fine concavo-convex shape formed by a phase separation structure of the resin component, or a fine concavo-convex shape corresponding to the shape of the particles may be used. Among them, in the cured product of a curable composition containing one or more curable resin precursor components, it is preferred to form a concave-convex shape by spinodal decomposition (wet spinodal decomposition) from a liquid phase, so that it contains particles (for example, thermoplastic resin particles such as polyamide particles, cross-linked poly(meth)acrylate particles, cross-linked polystyrene particles, cross-linked polymer particles such as cross-linked polyurethane particles, etc.) and a concave-convex shape formed by the shape of the particles. From the perspective of easily forming a concave-convex shape that can take into account both transparency and anti-glare properties, a concave-convex shape formed by wet spinodal decomposition is particularly preferred.
[0036] The anti-glare layer having a concave-convex shape formed by wet spinodal decomposition can be a cured product of a curable composition containing one or more polymer components and one or more curing resin precursor components. In detail, for the anti-glare layer, a composition (mixed liquid) containing one or more polymer components, one or more curing resin precursor components and a solvent is used. In the process of evaporating or removing the solvent from the liquid phase of the composition by drying, etc., phase separation based on spinodal decomposition occurs with the concentration of the mixed liquid, thereby forming a phase separation structure with a basic regularity of the interphase distance. More specifically, the above-mentioned wet spinodal decomposition can usually be carried out by applying the above-mentioned composition (uniform mixed liquid) to a support and evaporating the solvent from the coating layer. In the case of using a peelable support as the above-mentioned support, by peeling the anti-glare layer from the support, an anti-glare film consisting of the anti-glare layer alone can be obtained, and by using a transparent non-peelable support (transparent substrate layer) as a support, an anti-glare film of a laminated structure consisting of a transparent substrate layer and an anti-glare layer can be obtained.
[0037] (Polymer component)
[0038] As polymer component, thermoplastic resin can be usually used. As thermoplastic resin, as long as transparency is high and the above-mentioned surface concavoconvex shape can be formed by spinodal decomposition, it is not particularly limited, and examples thereof can be shown: styrene resin, (meth) acrylic polymer, organic acid vinyl ester polymer, vinyl ether polymer, halogen-containing resin, polyolefin (including alicyclic polyolefin), polycarbonate, polyester, polyamide, thermoplastic polyurethane, polysulfone resin (polyethersulfone, polysulfone, etc.), polyphenylene ether resin (polymer of 2,6-xylenol, etc.), cellulose derivatives (cellulose esters, cellulose carbamates, cellulose ethers, etc.), silicone resin (polydimethylsiloxane, polymethylphenylsiloxane, etc.), rubber or elastomer (diene rubbers such as polybutadiene, polyisoprene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylic rubber, urethane rubber, silicone rubber, etc.), etc. These thermoplastic resins can be used alone, or two or more are used in combination.
[0039] Among these polymer components, commonly used are styrene resins, (meth) acrylic polymers, vinyl acetate polymers, vinyl ether polymers, halogen-containing resins, alicyclic polyolefins, polycarbonates, polyesters, polyamides, cellulose derivatives, silicone resins, rubbers or elastomers, etc. In addition, as polymer components, non-crystalline and soluble polymer components in organic solvents (particularly a common solvent that can dissolve a variety of polymer components and cured resin precursor components) can be used. Particularly preferred polymer components with high formability or film-forming properties, transparency, and weather resistance are, for example, styrene resins, (meth) acrylic polymers, alicyclic polyolefins, polyester resins, cellulose derivatives (cellulose esters, etc.), and particularly preferred (meth) acrylic polymers and cellulose esters.
[0040] As the (meth)acrylic polymer, a homopolymer or copolymer of a (meth)acrylic monomer, a copolymer of a (meth)acrylic monomer and a copolymerizable monomer, etc. can be used. Examples of the (meth)acrylic monomer include: (meth)acrylic acid; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. (meth)acrylate C 1-10 Alkyl esters; (meth) aryl acrylates such as (meth) acrylate phenyl; (meth) acrylate hydroxyalkyl esters such as (meth) acrylate hydroxyethyl and (meth) acrylate hydroxypropyl; (meth) acrylate glycidyl; (meth) acrylate N, N-dialkylaminoalkyl (meth) acrylate; (meth) acrylonitrile; (meth) acrylates having an alicyclic hydrocarbon group such as tricyclodecane. Examples of copolymerizable monomers include styrene monomers such as styrene, vinyl ester monomers, maleic anhydride, maleic acid, fumaric acid, and the like. These monomers may be used alone or in combination of two or more.
[0041] Examples of (meth)acrylic polymers include poly(meth)acrylates such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers, (meth)acrylic acid ester-styrene copolymers (MS resins, etc.), etc. Among these, poly(meth)acrylic acid esters such as polymethyl methacrylate are preferred. 1-6 The alkyl ester is particularly a methyl methacrylate polymer containing methyl methacrylate as a main component (eg, about 50 to 100% by weight, preferably about 70 to 100% by weight).
[0042] Examples of cellulose esters include aliphatic organic acid esters (cellulose acetates such as cellulose diacetate and cellulose triacetate; cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose acetate butyrate, etc.); 1-6 aliphatic carboxylic acid esters, etc.), aromatic organic acid esters (cellulose phthalate, cellulose benzoate, etc. 7-12 Aromatic carboxylic acid esters), inorganic acid esters (e.g., cellulose phosphate, cellulose sulfate, etc.), etc., may also be mixed acid esters such as cellulose acetate / nitrocellulose esters. These cellulose esters may be used alone or in combination of two or more. Of these, cellulose diacetate, cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, etc. are preferred. 2-4 Cellulose acetate, particularly preferably cellulose acetate propionate or the like 3-4 Cellulose acid.
[0043] The polymer component [particularly a (meth)acrylic polymer] may be a polymer having a functional group that participates in the curing reaction (or a functional group that can react with a curing resin precursor component). The above-mentioned polymer may have a functional group in the main chain or in the side chain. The above-mentioned functional group may be introduced into the main chain by copolymerization, co-condensation, etc., but is usually introduced into the side chain. Examples of such functional groups include condensation groups, reactive groups (e.g., hydroxyl groups, acid anhydride groups, carboxyl groups, amino groups or imino groups, epoxy groups, glycidyl groups, isocyanate groups, etc.), polymerizable groups (e.g., vinyl groups, propenyl groups, isopropenyl groups, butenyl groups, allyl groups, etc.), and C 2-6 Alkenyl, ethynyl, propynyl, butynyl, etc. 2-6 Alkynyl, vinylidene, etc. 2-6 Alkenylene, or a group having these polymerizable groups [(meth)acryloyl group, etc.], etc. Among these functional groups, polymerizable groups are preferred.
[0044] Examples of a method for introducing a polymerizable group into a side chain include a method of reacting a thermoplastic resin having a functional group such as a reactive group or a condensable group with a polymerizable compound having a group reactive with the functional group.
[0045] In the thermoplastic resin having a functional group, examples of the functional group include a carboxyl group or an acid anhydride group thereof, a hydroxyl group, an amino group, and an epoxy group.
[0046] When the thermoplastic resin having a functional group is a thermoplastic resin having a carboxyl group or an acid anhydride group thereof, examples of polymerizable compounds having a group reactive with the functional group include polymerizable compounds having an epoxy group, a hydroxyl group, an amino group, an isocyanate group, and the like. Among these, polymerizable compounds having an epoxy group are commonly used, such as (meth)acrylate epoxycyclohexenyl ester and the like. 5-8Alkenyl esters, glycidyl (meth)acrylate, allyl glycidyl ether, and the like.
[0047] As a representative example, a thermoplastic resin having a carboxyl group or an anhydride group thereof, an epoxy-containing compound, in particular a (meth)acrylic polymer (such as a (meth)acrylic acid-(meth)acrylic acid ester copolymer), and a combination of epoxy-containing (meth)acrylic acid esters (such as epoxycycloalkenyl (meth)acrylic acid ester and glycidyl (meth)acrylic acid ester). Specifically, a polymer obtained by introducing a polymerizable unsaturated group into a part of the carboxyl group of a (meth)acrylic polymer can be used, for example, a (meth)acrylic polymer obtained by reacting a part of the carboxyl group of a (meth)acrylic acid-(meth)acrylic acid ester copolymer with an epoxy group of 3,4-epoxycyclohexenylmethyl acrylate to introduce a polymerizable group (photopolymerizable unsaturated group) into its side chain (CYCLOMER P, manufactured by Daicel Corporation) and the like.
[0048] The amount of the functional group (particularly polymerizable group) participating in the curing reaction introduced into the thermoplastic resin is, for example, about 0.001 to 10 mol, preferably about 0.01 to 5 mol, and more preferably about 0.02 to 3 mol, per 1 kg of the thermoplastic resin.
[0049] These polymer components can be used in combination as appropriate. That is, the polymer component can be composed of multiple polymers. Multiple polymers can be phase-separated by wet spinodal decomposition. In addition, multiple polymers may be incompatible with each other. In the case of combining multiple polymers, the combination of the first polymer and the second polymer is not particularly limited, and multiple polymers that are incompatible with each other near the processing temperature, such as two mutually incompatible polymers, can be used in appropriate combination. For example, in the case where the first polymer is a (meth)acrylic polymer (such as polymethyl methacrylate, a (meth)acrylic polymer having a polymerizable group, etc.), the second polymer can be a cellulose ester (cellulose acetate propionate, etc.) 3-4 acid cellulose, etc.), polyester (urethane-modified polyester, etc.).
[0050] Furthermore, from the perspective of scratch resistance after curing, it is preferred that at least one of the multiple polymers, for example one of the mutually incompatible polymers (at least one polymer when the first polymer and the second polymer are combined) is a polymer having a functional group (especially a polymerizable group) in the side chain that can react with the curing resin precursor component.
[0051] The weight ratio of the first polymer to the second polymer can be selected from the range of, for example, the former / the latter = 1 / 99 to 99 / 1, preferably from about 5 / 95 to 95 / 5. When the first polymer is a (meth)acrylic polymer and the second polymer is a cellulose ester, the weight ratio of the two polymers is, for example, the former / the latter = 50 / 50 to 99 / 1, preferably 55 / 45 to 90 / 10, further preferably 60 / 40 to 80 / 20 (particularly preferably 65 / 35 to 75 / 25).
[0052] In addition, as a polymer for forming a phase separation structure, in addition to the above-mentioned two incompatible polymers, the above-mentioned thermoplastic resin and other polymers may be included.
[0053] The glass transition temperature of the polymer component can be selected, for example, from the range of -100°C to 250°C, preferably -50°C to 230°C, and more preferably from about 0 to 200°C (for example, about 50 to 180°C). It should be noted that, from the viewpoint of surface hardness, it is advantageous for the glass transition temperature to be 50°C or higher (for example, about 70 to 200°C), preferably 100°C or higher (for example, about 100 to 170°C). The weight average molecular weight of the polymer component can be selected, for example, from the range of 1,000,000 or less, preferably from about 1,000 to 500,000.
[0054] (Curing resin precursor component)
[0055] As the curing resin precursor component, a compound having a functional group that reacts by heat, active energy rays (ultraviolet rays, electron beams, etc.) can be used, and various curable compounds that can be cured or crosslinked by heat, active energy rays, etc. to form a resin (particularly preferably a cured or crosslinked resin) can be used. As the above-mentioned curing resin precursor component, for example: thermosetting compounds or resins [low molecular weight compounds having epoxy groups, polymerizable groups, isocyanate groups, alkoxysilyl groups, silanol groups, etc. (for example, epoxy resins, unsaturated polyester resins, carbamate resins, silicone resins, etc.)]; photocurable compounds that can be cured by active light [ultraviolet rays, electron beams (EB), etc.] (ultraviolet curable compounds such as photocurable monomers and oligomers, electron beam curable compounds, etc.) and the like. It should be noted that sometimes photocurable compounds such as photocurable monomers, oligomers, and optionally low molecular weight photocurable resins are referred to as "photocurable resins" for short.
[0056] The photocurable compound includes, for example, a monomer and an oligomer (or a resin, particularly a low molecular weight resin).
[0057] Examples of the monomer include: monofunctional monomers [(meth)acrylic monomers such as (meth)acrylate, vinyl monomers such as vinyl pyrrolidone, (meth)acrylates having a bridged hydrocarbon group such as isobornyl (meth)acrylate and adamantyl (meth)acrylate], polyfunctional monomers having at least two polymerizable unsaturated bonds [alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and hexanediol di(meth)acrylate; diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyoxyethylene glycol di(meth)acrylate; (Poly)oxyalkylene glycol di(meth)acrylates such as tetramethylene glycol di(meth)acrylate; di(meth)acrylates having a bridged hydrocarbon group such as tricyclodecane dimethanol di(meth)acrylate and adamantane di(meth)acrylate; polyfunctional monomers having 3 to 6 polymerizable unsaturated bonds such as glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate] and the like.
[0058] Examples of the oligomer or resin include (meth)acrylates of bisphenol A-alkylene oxide adducts, epoxy (meth)acrylates [bisphenol A type epoxy (meth)acrylates, novolac type epoxy (meth)acrylates, etc.], polyester (meth)acrylates [for example, aliphatic polyester type (meth)acrylates, aromatic polyester type (meth)acrylates, etc.], (poly)urethane (meth)acrylates [polyester type urethane (meth)acrylates, polyether type urethane (meth)acrylates, etc.], silicone (meth)acrylates, and the like.
[0059] These photocurable compounds can be used alone or in combination of two or more. Among these, preferred are photocurable compounds that can be cured in a short time, such as ultraviolet curable compounds (monomers, oligomers, optionally low molecular weight resins, etc.), and EB curable compounds. In particular, the photocurable compounds (resin precursor components) that are advantageous for practical use are ultraviolet curable compounds. Furthermore, in order to improve resistance such as scratch resistance, it is preferred that the photocurable compound is a compound having 2 or more (preferably 2 to 6, more preferably about 2 to 4) polymerizable unsaturated bonds in the molecule.
[0060] The weight average molecular weight of the curable resin precursor component is not particularly limited, but is, for example, about 5000 or less, preferably 2000 or less, and more preferably about 1000 or less in terms of polystyrene in gel permeation chromatography (GPC), taking into account compatibility with the polymer.
[0061] In order to improve the transparency and anti-glare property of the anti-glare film, the curable resin precursor component may contain a filler and / or a fluorine atom depending on the type of the component.
[0062] The filler may include inorganic particles such as silica particles, titanium oxide particles, zirconium oxide particles, and aluminum oxide particles, and organic particles such as crosslinked (meth)acrylic polymer particles and crosslinked styrene resin particles. These fillers may be used alone or in combination of two or more.
[0063] Among these fillers, nanometer-sized silica particles (silicon dioxide nanoparticles) are preferred from the perspective of excellent optical properties and easy formation of concave-convex shapes that can take into account transparency and anti-glare properties through spinodal decomposition. From the perspective of being able to suppress the yellowness of the anti-glare film, the silicon dioxide nanoparticles are preferably solid silicon dioxide nanoparticles. In addition, the average particle size of the silicon dioxide nanoparticles is, for example, 1 to 800 nm, preferably 3 to 500 nm, and more preferably about 5 to 300 nm.
[0064] The ratio of the filler (particularly silica nanoparticles) to the entire curing resin precursor component may be about 10 to 90 wt %, for example, 10 to 80 wt %, preferably 15 to 70 wt %, more preferably about 20 to 50 wt %.
[0065] As the precursor component containing fluorine atoms (fluorine-containing curable compound or fluorine-based compound with polymerizable group), the fluoride of the above-mentioned monomer and oligomer can be listed, for example, fluoroalkyl (meth) acrylate [for example, perfluorooctylethyl (meth) acrylate, trifluoroethyl (meth) acrylate, etc.], fluoro (poly) oxyalkylene glycol di (meth) acrylate [for example, fluoroethylene glycol di (meth) acrylate, fluoropolyethylene glycol di (meth) acrylate, fluoropropylene glycol di (meth) acrylate, etc.], fluorine-containing epoxy resin, fluorine-containing urethane resin, etc. Among these, preferably there is a fluorinated polyether compound with a (meth) acryloyl group. The fluorine-containing curable compound can also be a commercially available fluorine-based polymerizable leveling agent.
[0066] The curing resin precursor component may further contain a curing agent according to its type. For example, in a thermosetting resin, a curing agent such as an amine or a polycarboxylic acid may be contained, and in a photocurable resin, a photopolymerization initiator may be contained. As the photopolymerization initiator, commonly used components such as acetophenones or propiophenones, benzyls, benzoins, benzophenones, thioxanthones, acylphosphine oxides, etc. can be exemplified. Relative to the entire curing resin precursor component, the proportion of the curing agent such as the photopolymerization initiator is, for example, 0.1 to 20% by weight, preferably 0.5 to 10% by weight, and more preferably about 1 to 8% by weight.
[0067] The curable resin precursor component may further contain a curing accelerator. For example, the photocurable resin may contain a photocuring accelerator such as a tertiary amine (dialkylaminobenzoic acid ester, etc.), a phosphine-based photopolymerization accelerator, and the like.
[0068] Among these curing resin precursor components, preferred are multifunctional (meth)acrylates (e.g., (meth)acrylates having 2 to 8 polymerizable groups such as dipentaerythritol hexa(meth)acrylate, etc.), epoxy (meth)acrylates, polyester (meth)acrylates, urethane (meth)acrylates, silicone (meth)acrylates, etc. In addition, the curing resin precursor component preferably contains silica nanoparticles and / or fluorine atoms, and particularly preferably contains a photocurable compound containing silica nanoparticles [especially multifunctional (meth)acrylates containing silica nanoparticles, urethane (meth)acrylates containing silica nanoparticles, silicone (meth)acrylates containing silica nanoparticles] and a fluorine-containing curable compound.
[0069] Preferred combinations of curable resin precursor components include, for example, a combination of a photocurable compound containing silica nanoparticles and a silicone (meth) acrylate, a combination of urethane (meth) acrylate, a 3-6 functional (meth) acrylate, a silicone (meth) acrylate and a fluorine-containing curable compound, and a combination of a photocurable compound containing silica nanoparticles and a fluorine-containing curable compound. A particularly preferred combination is a combination of a photocurable compound containing silica nanoparticles and a fluorine-containing curable compound.
[0070] In the present invention, from the aspect of easily forming a concavo-convex shape that can take into account both transparency and anti-glare properties, in order to make the silica nanoparticles reach the above ratio relative to the entire cured resin precursor component, it is preferred that the cured resin precursor component contains a cured resin precursor component containing silica nanoparticles. In addition, relative to the entire cured resin precursor component, the ratio of the fluorine-containing curable compound is, for example, 0.001 to 1% by weight (e.g., 0.01 to 0.5% by weight), preferably 0.02 to 0.3% by weight (e.g., 0.03 to 0.2% by weight), and more preferably about 0.05 to 0.1% by weight.
[0071] (Combination of polymer component and curable resin precursor component)
[0072] In the present invention, at least two of the above-mentioned polymer components and the above-mentioned curing resin precursor components are used in a combination that undergoes phase separation near the processing temperature. As a combination that undergoes phase separation, for example: (a) a combination in which multiple polymer components are incompatible with each other and undergo phase separation; (b) a combination in which a polymer component and a curing resin precursor component are incompatible and undergo phase separation; (c) a combination in which multiple curing resin precursor components are incompatible with each other and undergo phase separation, etc. Among these combinations, (a) a combination of multiple polymer components, (b) a combination of a polymer component and a curing resin precursor component are generally preferred, and (a) a combination of multiple polymer components is particularly preferred. In the case where the compatibility of the two components that undergo phase separation is high, the two components will not effectively undergo phase separation during the drying process for evaporating the solvent, and the function as an anti-glare layer is reduced.
[0073] It should be noted that the polymer component and the curing resin precursor component are usually incompatible with each other. In the case where the polymer component and the curing resin precursor component are incompatible and phase separation occurs, a variety of polymer components can be used as the polymer component. In the case of using a variety of polymer components, at least one polymer component is incompatible with the curing resin precursor component, and the other polymer components can be compatible with the above-mentioned curing resin precursor component. In addition, it can also be a combination of two incompatible polymer components and a curing resin precursor component (particularly a monomer or oligomer with multiple curable functional groups).
[0074] In the case where the polymer component is composed of multiple incompatible polymer components and phase separation occurs, the curing resin precursor component can be used in a combination that is compatible with at least one polymer component of the multiple incompatible polymers near the processing temperature. That is, for example, in the case where multiple incompatible polymer components are composed of the first polymer and the second polymer, the curing resin precursor component can be compatible with any polymer of the first polymer or the second polymer, and can also be compatible with both polymer components, but more preferably only compatible with one polymer component. In the case of compatibility with the two polymer components, it will be phase-separated into at least two phases of a mixture with the first polymer and the curing resin precursor component as the main components, and a mixture with the second polymer and the curing resin precursor component as the main components.
[0075] When the compatibility of the selected multiple polymer components is high, the polymer components will not be effectively phase-separated from each other during the drying process for evaporating the solvent, and the function as an anti-glare layer is reduced. The phase separation of the multiple polymer components can be easily determined by the following operation: a uniform solution is prepared using a solvent that is a good solvent for the two components, and in the process of slowly evaporating the solvent, it is confirmed by visual observation whether the remaining solid component is turbid.
[0076] In addition, the refractive index of the cured or cross-linked resin generated by the polymer component and the cured resin precursor component by curing is usually different from each other. In addition, the refractive indexes of the multiple polymer components (the first polymer and the second polymer) are also different from each other. The difference in refractive index between the polymer component and the cured or cross-linked resin and the difference in refractive index between the multiple polymer components (the first polymer and the second polymer) can be, for example, 0.001 to 0.2, preferably about 0.05 to 0.15.
[0077] The ratio (weight ratio) of the polymer component to the curing resin precursor component is not particularly limited, and can be selected from the range of, for example, the former / the latter = 1 / 99 to 95 / 5, for example, 2 / 98 to 90 / 10, preferably 3 / 97 to 80 / 20, and more preferably 5 / 95 to 70 / 30. In addition, when the curing resin precursor component contains a photocurable compound containing silica nanoparticles, the above ratio can be, for example, 2 / 98 to 30 / 70, preferably 3 / 97 to 20 / 80, and more preferably 5 / 95 to 15 / 85. In addition, when the curing resin precursor component does not contain a photocurable compound containing silica nanoparticles, the above ratio can be, for example, 10 / 90 to 60 / 40, preferably 20 / 80 to 50 / 50, and more preferably 30 / 70 to 40 / 60.
[0078] (Other ingredients)
[0079] The anti-glare layer formed by the composition containing the resin component may contain various additives, for example: leveling agent, stabilizer (antioxidant, ultraviolet absorber, etc.), surfactant, water-soluble polymer, filler, crosslinking agent, coupling agent, colorant, flame retardant, lubricant, wax, preservative, viscosity modifier, tackifier, defoamer, etc. The total proportion of the additives is, for example, about 0.01 to 10% by weight (particularly preferably 0.1 to 5% by weight) relative to the entire anti-glare layer.
[0080] (Thickness of anti-glare layer)
[0081] The thickness (average thickness) of the anti-glare layer may be, for example, about 0.3 to 20 μm, preferably about 1 to 15 μm (for example, 1 to 10 μm), and usually about 3 to 12 μm (particularly about 4 to 10 μm). It should be noted that, when the anti-glare layer alone constitutes the anti-glare film, the thickness (average thickness) of the anti-glare layer is, for example, about 1 to 100 μm, preferably about 3 to 50 μm.
[0082] (Transparent base material layer)
[0083] The transparent substrate layer may be formed of a transparent material, which may be selected according to the application, and may be an inorganic material such as glass, but organic materials are commonly used in view of strength, formability, etc. Examples of organic materials include cellulose derivatives, polyesters, polyamides, polyimides, polycarbonates, (meth) acrylic polymers, etc. Among these, cellulose esters, polyesters, etc. are commonly used.
[0084] Examples of cellulose esters include cellulose acetate such as triacetyl cellulose (TAC), cellulose acetate propionate, and cellulose acetate butyrate. 3-4 Examples of the polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).
[0085] Among these, poly(C) such as PET and PEN are preferred from the viewpoint of excellent balance in mechanical properties, transparency, etc. 2-4 Alkylene aromatic esters.
[0086] The transparent base material layer may contain conventional additives listed as examples in the section of the anti-glare layer, and the proportion of the additives is the same as that of the anti-glare layer.
[0087] The transparent base material layer may be a uniaxially or biaxially stretched film, but may be an unstretched film from the viewpoint of low birefringence and excellent optical isotropy.
[0088] The transparent base material layer may be subjected to a surface treatment (eg, corona discharge treatment, flame treatment, plasma treatment, ozone treatment, ultraviolet irradiation treatment, etc.), or may have an easy-adhesion layer.
[0089] The thickness (average thickness) of the transparent base material layer is, for example, about 5 to 2000 μm, preferably about 15 to 1000 μm, and more preferably about 20 to 500 μm.
[0090] (Adhesive layer)
[0091] The anti-glare film of the present invention can be used as a protective film for various touch panel display devices including smartphones, PCs (tablet PCs, etc.), etc. In these applications, an adhesive layer may be formed on at least a portion of the other surface of the transparent substrate layer.
[0092] The adhesive layer is formed by a conventional transparent adhesive. Examples of adhesives include rubber adhesives, acrylic adhesives, olefin adhesives (modified olefin adhesives, etc.), silicone adhesives, etc. Among these adhesives, silicone adhesives are preferred in terms of optical properties, reoperability, etc.
[0093] The thickness (average thickness) of the adhesive layer is, for example, about 1 to 150 μm, preferably 10 to 100 μm, more preferably 20 to 70 μm (particularly preferably 25 to 50 μm).
[0094] The adhesive layer may be formed on the entire other surface or on a portion of the other surface (e.g., the peripheral portion). In addition, when formed on the peripheral portion, a frame-shaped member may be formed on the peripheral portion of the anti-glare film (e.g., a plastic sheet may be laminated on the peripheral portion) for the purpose of improving the handling properties for lamination, and the adhesive layer may be formed on the frame-shaped member.
[0095] [Method for producing anti-glare film]
[0096] The method for manufacturing the anti-glare film of the present invention is not particularly limited and can be appropriately selected according to the type of material. It can be formed by physical processing, transfer using a mold, etc., but in terms of productivity, it is preferably manufactured by a curing step of curing the curable composition by heat or active energy rays. In particular, for an anti-glare film comprising an anti-glare layer having a concave-convex shape formed by wet spinodal decomposition, it can be a method that undergoes the following steps: a phase separation step in which a curable composition containing one or more polymer components and one or more curable resin precursor components is coated on a support (especially a transparent substrate layer) and dried, thereby causing at least two components selected from the polymer components and the curable resin precursor components to undergo phase separation by wet spinodal decomposition; a curing step in which the curable composition after phase separation is cured by heat or active energy rays.
[0097] In the phase separation process, the curable composition may contain a solvent. The solvent may be selected according to the type and solubility of the above-mentioned polymer components and curing resin precursor components, as long as it is a solvent that can at least uniformly dissolve the solid components (such as multiple polymer components and curing resin precursor components, reaction initiators, and other additives). In particular, the phase separation structure can also be controlled by adjusting the solubility of the solvent in the polymer components and the curing resin precursor. Examples of such solvents include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dimethyl ether, di ... The solvent may be selected from the group consisting of alkylene, tetrahydrofuran, etc., aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated hydrocarbons (methylene chloride, ethylene dichloride, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), water, alcohols (ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves [methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether (1-methoxy-2-propanol), etc.], cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc. The solvent may also be a mixed solvent.
[0098] Among these solvents, solvents containing ketones such as methyl ethyl ketone are preferred, and mixed solvents of ketones and alcohols (such as butanol) and / or cellosolves (such as 1-methoxy-2-propanol) are particularly preferred. In the mixed solvent, the ratio of alcohols and / or cellosolves (when the two are mixed, the total amount) to 100 parts by weight of ketones is, for example, 10 to 150 parts by weight, preferably 15 to 100 parts by weight, and more preferably 20 to 80 parts by weight (especially preferably 25 to 50 parts by weight). When alcohols and cellosolves are combined, the ratio of cellosolves to 100 parts by weight of alcohols is, for example, 1 to 100 parts by weight, preferably 10 to 80 parts by weight, and more preferably 30 to 70 parts by weight (especially preferably 40 to 60 parts by weight). In the present invention, by appropriately combining solvents, phase separation based on spinodal decomposition can be adjusted, and a concavo-convex shape that can take both transparency and anti-glare properties into consideration can be formed.
[0099] The concentration of the solute (polymer component, curing resin precursor component, reaction initiator, other additives) in the mixed solution can be selected within the range that does not impair the phase separation and the range of castability, coating properties, etc., for example, 1 to 80 weight %, preferably 10 to 70 weight %, more preferably 20 to 60 weight % (particularly preferably 30 to 55 weight %).
[0100] As the coating method, commonly used methods can be listed, such as roll coating, air knife coating, blade coating, rod coating, reverse coating, wire rod coating, notch wheel coating, dip / squeeze coating, die coating, gravure coating, micro gravure coating, screen coating, dip coating, spray coating, spin coating, etc. Among these methods, wire rod coating, gravure coating, etc. are commonly used. It should be noted that, as required, the coating liquid can also be coated multiple times.
[0101] After the mixed solution is cast or coated, the phase separation based on spinodal decomposition can be induced by evaporating the solvent at a temperature lower than the boiling point of the solvent (e.g., 1 to 120°C lower, preferably 5 to 50°C lower, and particularly preferably 10 to 50°C lower than the boiling point of the solvent). The evaporation of the solvent can usually be carried out by drying, for example, at a temperature corresponding to the boiling point of the solvent, for example, 30 to 200°C (e.g., 30 to 100°C), preferably 40 to 120°C, and more preferably 50 to 90°C (particularly preferably 60 to 85°C).
[0102] The spinodal decomposition that occurs with the evaporation of the solvent can impart order or periodicity to the average distance between domains of the phase separation structure.
[0103] In the curing step, the dried curable composition is finally cured by active light (ultraviolet rays, electron beams, etc.), heat, etc., so that the phase separation structure formed by spinodal decomposition can be immediately fixed. The curing of the curable composition can be combined with heating, light, etc. depending on the type of the curable resin precursor component.
[0104] The heating temperature can be selected from an appropriate range, for example, about 50 to 150° C. The light irradiation can be selected according to the type of the photocurable component, etc., and usually ultraviolet rays, electron beams, etc. can be used. The commonly used light source is usually an ultraviolet irradiation device.
[0105] As the light source, for example, in the case of ultraviolet rays, Deep UV lamps, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, halogen lamps, laser light sources (light sources such as helium-cadmium lasers and excimer lasers) etc. can be used. The irradiation light amount (irradiation energy) varies depending on the thickness of the coating film, for example, 10 to 10000 mJ / cm 2 , preferably 20 to 5000 mJ / cm 2 , more preferably 30 to 3000 mJ / cm 2 If necessary, the illumination can also be carried out in an inert gas atmosphere.
[0106] [Display device]
[0107] The anti-glare film of the present invention can achieve both transparency and anti-glare properties, and therefore can be used as an optical component of various display devices, such as liquid crystal displays (LCDs), organic EL displays, and display devices with touch panels. In particular, it is useful as an optical element for LCDs and organic EL displays.
[0108] In detail, the LCD may be a reflective LCD that utilizes external light to illuminate a display unit having a liquid crystal unit, or a transmissive LCD that has a backlight unit for illuminating the display unit. In a reflective LCD, incident light from the outside may be introduced via the display unit, and the transmitted light that passes through the display unit may be reflected by a reflective component, thereby illuminating the display unit. In a reflective LCD, the anti-glare film of the present invention may be disposed in the optical path located in front of the above-mentioned reflective component. For example, the anti-glare film of the present invention may be disposed or laminated on the front surface (visible side front surface) of the display unit, etc., and in particular, may be disposed on the front surface of an LCD having a collimated backlight unit and not having a prism sheet.
[0109] In a transmissive LCD, the backlight unit may include a light guide plate (e.g., a light guide plate with a wedge-shaped cross section) for allowing light from a light source (a tubular light source such as a cold cathode tube, a point light source such as a light emitting diode, etc.) to be incident from one side and to be emitted from an exit surface on the front surface. In addition, as required, a prism sheet may be provided on the front surface side of the light guide plate. It should be noted that a reflective member for reflecting light from the light source toward the exit surface side is usually provided on the back side of the light guide plate. In such a transmissive LCD, the anti-glare film of the present invention may usually be provided in the light path in front of the light source. For example, the anti-glare film of the present invention described above may be provided between the light guide plate and the display unit, on the front surface of the display unit, etc.
[0110] In an organic EL display, each pixel of the organic EL is constituted by a light-emitting element, which is usually formed by a cathode electrode such as metal / electron injection layer / electron transport layer / light-emitting layer / hole transport layer / hole injection layer / anode electrode such as indium tin oxide (ITO) / a substrate such as a glass plate or a transparent plastic plate. In an organic EL display, the anti-glare film of the present invention can be arranged in the light path.
[0111] In addition, the anti-glare film of the present invention can be used as an aftermarket protection or protective film for preventing LCDs (including LCDs that also serve as display devices with touch panels) and organic EL displays (including organic EL displays that also serve as display devices with touch panels) from being damaged.
[0112] Example
[0113] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples. The raw materials used in Examples and Comparative Examples are as follows, and the obtained anti-glare films were evaluated by the following methods.
[0114] [raw material]
[0115] Acrylic polymer having a polymerizable group: "CYCLOMER P" manufactured by Daicel Allnex Corporation
[0116] Cellulose acetate propionate: "CAP-482-20" manufactured by Eastman Co., Ltd., degree of acetylation = 2.5%, degree of propionylation = 46%, number average molecular weight in terms of polystyrene: 75,000
[0117] Silicone acrylate: EB1360 manufactured by Daicel Allnex Corporation
[0118] Silicone hard coating material: "AS-201S" manufactured by Tokushiki Co., Ltd.
[0119] Urethane acrylate A: "U-15HA" manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0120] Urethane acrylate B: "AU-230" manufactured by Tokushiki Co., Ltd.
[0121] Dipentaerythritol hexaacrylate: "DPHA" manufactured by DAICEL ALLNEX Co., Ltd.
[0122] Nanosilica-containing acrylic UV-curable compound: "XR39-C6210" manufactured by Momentive Performance Materials Japan Co., Ltd.
[0123] Silica-containing acrylic UV-curable compound: "Z-757-4RL" manufactured by AICA Industries, Ltd.
[0124] Acrylic UV curable compound: "Z-757-4CL" manufactured by AICA INDUSTRY CO., LTD. PMMA beads A: "SSX-115" manufactured by SEKISUI CHEMICAL CO., LTD.
[0125] PMMA beads B: "SSX-105" manufactured by Sekisui Chemical Co., Ltd.
[0126] Cross-linked styrene beads: "SX-130H" manufactured by Soken Chemical Co., Ltd.
[0127] Fluorine compound A having a polymerizable group: "KY-1203" manufactured by Shin-Etsu Chemical Co., Ltd.
[0128] Fluorine compound B having a polymerizable group: "FTERGENT 602A" manufactured by NEOS Corporation
[0129] Photoinitiator A: "IRGACURE 184" manufactured by BASF Japan Co., Ltd.
[0130] Photoinitiator B: "IRGACURE 907" manufactured by BASF Japan Co., Ltd.
[0131] Polyethylene terephthalate (PET) film: "DIAFOIL" manufactured by Mitsubishi Plastics Corporation
[0132] Triacetyl cellulose (TAC) film: “FUJITACT TG60UL” manufactured by FUJIFILM Corporation.
[0133] [Coating thickness]
[0134] The optical film thickness meter was used to measure 10 random locations, and the average value was calculated.
[0135] [Haze]
[0136] The haze meter ("NDH-5000W" manufactured by Nippon Denshoku Co., Ltd.) was used and the measurement was performed in accordance with JIS K7136, with the surface having the concavo-convex structure being arranged to face the light receiving side.
[0137] [Transmitted hue(b * )]
[0138] The measurement was performed using a spectrophotometer ("U-3010" manufactured by Hitachi High-Tech Science Co., Ltd.) in accordance with JIS Z8781.
[0139] [60° gloss]
[0140] The glossiness was measured at an angle of 60° using a gloss meter ("IG-320" manufactured by Horiba, Ltd.) in accordance with JIS K7105.
[0141] [Anti-glare]
[0142] The produced anti-glare film was attached to a commercially available black acrylic plate using an optical paste, and a reflected image when irradiated with a three-wavelength fluorescent lamp was confirmed by visual observation and evaluated according to the following criteria.
[0143] ◎: Fluorescent light is not visible at all
[0144] ○: The outline of the fluorescent lamp is blurred
[0145] △: The shape of the fluorescent lamp can be seen, but the glare is suppressed.
[0146] [tone]
[0147] The produced anti-glare film was directed toward a three-wavelength fluorescent lamp, and the color tone of the transmitted light was observed with the naked eye and evaluated according to the following criteria.
[0148] ○: When the film is observed through a fluorescent light, it is observed to be colorless and transparent
[0149] △: Slightly yellowish or bluish
[0150] ×: Yellow or blue is clearly observed.
[0151] [Example 1]
[0152] A solution was prepared by dissolving 15.0 parts by weight of an acrylic polymer having a polymerizable group, 3 parts by weight of cellulose acetate propionate, 150 parts by weight of an acrylic ultraviolet curable compound containing nanosilica, and 1 part by weight of silicone acrylate in a mixed solvent of 101 parts by weight of methyl ethyl ketone and 24 parts by weight of 1-butanol.
[0153] The solution was cast onto a PET film using a wire bar (#20), and then placed in an oven at 80° C. for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 9 μm.
[0154] Then, the coating was irradiated with ultraviolet light for about 5 seconds (the accumulated light intensity was about 100 mJ / cm 2 The coating was cured by ultraviolet light to obtain an anti-glare film.
[0155] [Example 2]
[0156] A solution was prepared by dissolving 12.5 parts by weight of an acrylic polymer having a polymerizable group, 4 parts by weight of cellulose acetate propionate, 150 parts by weight of an acrylic ultraviolet curable compound containing nanosilica, and 1 part by weight of silicone acrylate in a mixed solvent of 81 parts by weight of methyl ethyl ketone, 24 parts by weight of 1-butanol, and 13 parts by weight of 1-methoxy-2-propanol.
[0157] The solution was cast onto a PET film using a wire bar (#20), and then placed in an oven at 80° C. for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 9 μm.
[0158] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0159] [Example 3]
[0160] A solution was prepared by dissolving 45.6 parts by weight of an acrylic polymer having a polymerizable group, 2.3 parts by weight of cellulose acetate propionate, 70.7 parts by weight of urethane acrylate A, 8.2 parts by weight of dipentaerythritol hexaacrylate, 0.6 parts by weight of silicone acrylate, 0.1 parts by weight of a fluorine compound B having a polymerizable group, 1 part by weight of a photoinitiator A, and 1 part by weight of a photoinitiator B in a mixed solvent of 128 parts by weight of methyl ethyl ketone, 25 parts by weight of 1-butanol, and 31 parts by weight of cyclohexanone.
[0161] The solution was cast onto a TAC film using a wire bar (#16), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 7 μm.
[0162] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0163] [Example 4]
[0164] A solution was prepared by dissolving 12.5 parts by weight of an acrylic polymer having a polymerizable group, 5.5 parts by weight of cellulose acetate propionate, 149 parts by weight of an acrylic ultraviolet curable compound containing nanosilica, and 0.1 parts by weight of a fluorine compound B having a polymerizable group in a mixed solvent of 129 parts by weight of methyl ethyl ketone, 24 parts by weight of 1-butanol, and 13 parts by weight of 1-methoxy-2-propanol.
[0165] The solution was cast onto a PET film using a wire bar (#14), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 5 μm.
[0166] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0167] [Example 5]
[0168] A solution was prepared by dissolving 36.9 parts by weight of an acrylic polymer having a polymerizable group, 3.0 parts by weight of cellulose acetate propionate, 55.0 parts by weight of urethane acrylate A, 0.7 parts by weight of silicone acrylate, 22.9 parts by weight of dipentaerythritol hexaacrylate, 0.1 parts by weight of a fluorine compound A having a polymerizable group, 1 part by weight of a photoinitiator A, and 1 part by weight of a photoinitiator B in a mixed solvent of 144 parts by weight of methyl ethyl ketone and 21 parts by weight of 1-butanol.
[0169] The solution was cast onto a TAC film using a wire bar (#18), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 8 μm.
[0170] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0171] [Example 6]
[0172] A solution was prepared by dissolving 50 parts by weight of an acrylic polymer having a polymerizable group, 4 parts by weight of cellulose acetate propionate, 76 parts by weight of urethane acrylate A, 1 part by weight of silicone acrylate, 1 part by weight of photoinitiator A, and 1 part by weight of photoinitiator B in a mixed solvent of 176 parts by weight of methyl ethyl ketone and 28 parts by weight of 1-butanol.
[0173] The solution was cast onto a TAC film using a wire bar (#18), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 8 μm.
[0174] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0175] [Example 7]
[0176] 3 parts by weight of cellulose acetate propionate, 97 parts by weight of urethane acrylate A, 90 parts by weight of PMMA beads B, 1 part by weight of photoinitiator A, and 1 part by weight of photoinitiator B were dissolved in a mixed solvent of 277 parts by weight of methyl ethyl ketone and 23 parts by weight of 1-butanol to prepare a solution.
[0177] The solution was cast onto a PET film using a wire bar (#6), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating layer with a thickness of about 1 μm.
[0178] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0179] [Reference Example 1]
[0180] 39 parts by weight of urethane acrylate B, 15.7 parts by weight of a silicone-based hard coating material, 0.3 parts by weight of PMMA beads A, and 6.1 parts by weight of cross-linked styrene beads were dissolved in 38 parts by weight of methyl ethyl ketone to prepare a solution.
[0181] The solution was cast onto a PET film using a wire bar (#14), and then placed in an oven at 100°C for 1 minute to evaporate the solvent, thereby forming a coating with a thickness of about 6 μm.
[0182] Then, the coating layer was irradiated with ultraviolet light for about 5 seconds using a high-pressure mercury lamp to perform ultraviolet curing treatment on the coating layer, thereby obtaining an anti-glare film.
[0183] [Reference Example 2]
[0184] A solution was prepared by mixing 50 parts by mass of a silicon dioxide-containing acrylic ultraviolet curable compound and 150 parts by mass of an acrylic ultraviolet curable compound. The solution was cast onto a PET film using a wire rod (#14), and then placed in an oven at 80°C for 1 minute to evaporate the solvent, forming a coating with a thickness of about 7 μm.
[0185] Then, the coating layer was irradiated with ultraviolet rays for about 5 seconds using an ultraviolet lamp to perform ultraviolet curing treatment, thereby obtaining an anti-glare film.
[0186] Table 1 shows the evaluation results of the anti-glare films obtained in Examples and Reference Examples.
[0187] [Table 1]
[0188]
[0189] As is clear from the results in Table 1, the anti-glare films of Examples have high anti-glare properties and are also excellent in color tone (colorless transparency).
[0190] Industrial Applicability
[0191] The anti-glare film of the present invention can be used as an anti-glare film in various display devices, such as LCD, cathode tube display device, organic or inorganic EL display, field emission display (FED), surface electric field display (SED), rear projection television display, plasma display, display device with touch panel, etc.
[0192] In addition, the anti-glare film of the present invention can correspond to screens of various sizes, and can be used for display devices with small or portable screens (such as displays for car navigation systems, game consoles, smart phones, tablet PCs, etc., and display devices with touch panels, etc.), display devices with medium-sized screens (such as notebook or portable PCs, PCs such as desktop PCs, TVs, etc.), display devices with large screens (such as digital signage, etc.), etc. Among these, it can be appropriately selected according to the difference in resolution, but from the aspect of being able to take into account both transparency and anti-glare properties, it can be suitably used for display devices such as medium-sized screens and large screens.
[0193] Furthermore, since the film whose anti-glare layer contains a cured resin precursor component is also excellent in scratch resistance, it can also be used as a protective film for LCD and organic EL displays in the aftermarket.
Claims
1. An anti-glare film comprising a transparent substrate layer and an anti-glare layer formed on at least one side of the transparent substrate layer, wherein the chromaticity b of the transmitted light is * The absolute value of is less than 3, the glossiness at 60° is 0.3-5%, and the haze is 70-97%. The anti-glare layer is a cured product of a curable composition containing one or more polymer components and one or more curable resin precursor components. The curable resin precursor component contains silica nanoparticles, and the ratio of the silica nanoparticles to the entire curable resin precursor component is 10 to 90 weight %.
2. The anti-glare film according to claim 1, wherein: At least two components selected from the group consisting of the polymer component and the curing resin precursor component are capable of phase separation by wet spinodal decomposition.
3. The anti-glare film according to claim 1 or 2, wherein: The polymer component contains cellulose esters and / or a (meth)acrylic polymer which may have a polymerizable group.
4. The anti-glare film according to claim 1 or 2, wherein: The curable resin precursor component contains at least one selected from the group consisting of polyfunctional (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, urethane (meth)acrylate, and silicone (meth)acrylate.
5. The anti-glare film according to claim 1 or 2, wherein: The curable resin precursor component contains silica nanoparticles and fluorine atoms.
6. A method for producing an anti-glare film, which is a method for producing the anti-glare film according to any one of claims 1 to 5, the method comprising: A curing step of curing the curable composition by heat or active energy rays.
7. The method for manufacturing an anti-glare film according to claim 6, further comprising: A phase separation step in which a curable composition containing one or more polymer components and one or more curable resin precursor components is applied to a support and dried to separate at least two components selected from the polymer components and the curable resin precursor components by wet spinodal decomposition. The curing step is a step of curing the curable composition after phase separation by heat or active energy rays. 8 . A display device comprising the anti-glare film according to claim 1 . 9 . The display device according to claim 8 , which is an organic EL display or a liquid crystal display.
10. A method for improving the anti-glare property and transparency of an anti-glare film, the method comprising: The chromaticity of the transmitted light b * The absolute value of , 60° glossiness and haze are adjusted to less than 3, 0.3-5% and 70-97% respectively to improve the anti-glare property and transparency of the anti-glare film. The anti-glare film comprises a transparent substrate layer and an anti-glare layer formed on at least one side of the transparent substrate layer, wherein the anti-glare layer is a cured product of a curable composition containing one or more polymer components and one or more curable resin precursor components. The curable resin precursor component contains silica nanoparticles, and the ratio of the silica nanoparticles to the entire curable resin precursor component is 10 to 90 weight %.
Citation Information
Patent Citations
Muting circuit of FM receiver
JP1980031388A
Anti-glare film and method for manufacturing the same
JP2014085371A
Anti-glare film, method for producing same, and use thereof
CN111448488A
Light scattering film, method for manufacturing light scattering film, polarizing plate and liquid crystal display device
JP2003121618A
Protective film for polarizing plate, the polarizing plate and liquid crystal display
JP2008158483A